Distributed filtering for time-varying systems over sensor networks with randomly switching topologies under the Round-Robin protocol - Bu, Xianye; Dong, Hongli; Han, Fei; Hou, Nan; Li, Gongfa (Neurocomputing (Amsterdam), 2019)
This paper focuses on the filtering problem for nonlinear systems over sensor networks whose topologies are changeable subject to Round-Robin (RR) protocol in the finite horizon case. The phenomenon of switching topologies for sensor networks is considered due to the weak connections between the node and its neighbors. The Round-Robin communication strategy is employed to save the limited bandwidth and reduce the network resource consumption. It is our target to design distributed filters so that the dynamics of augmented error system satisfies the given level of average H∞ performance. We get the sufficient conditions in order to guarantee the existence of the desired distributed filters whose parameter matrices would be attained by a recursive method in terms of a set of matrix inequalities. In the end, a numerical simulation is exploited to describe the validity of the raised filter design technique.